Respuesta :

Answer:

Inverse function: A function g is the inverse of a function f if whenever y=f(x) then x=g(y).

In other words, we can write this in terms of the composition of f and g as g(f(x))=x.

For any input x, the function corresponding to f spits out the value y=f(x)=4x+12.

Now, we want to find the inverse function g(x)=[tex]f^{-1}[/tex] that takes the value y as an input and spits out x as the output.

In other words, y=f(x) gives y as a function of x and we want to find [tex]x=f^{-1}(y)[/tex] that will give us x as a function of y.

Given,the expression y=4x+12 for y as a function of x and solve for x.

Subtract 12 from both sides we get;

y-12 = 4x+12-12

Simplify:

y-12 = 4x

Divide by 4 to both sides we get;

[tex]\frac{y-12}{4} =\frac{4x}{4}[/tex]

Simplify:

[tex]x=\frac{1}{4}y - 3[/tex]

therefore,  [tex]x = f^{-1}(y) = \frac{1}{4}y-3[/tex]

since, g(x) is the inverse of f(x)

⇒[tex] g(x)=\frac{1}{4}x-3[/tex]

Now, verify that g(x) is really the inverse of f(x), we should show that the composition of f and g doesn't do anything to the input.

[tex](g o f)(x) = g(f(x)) = g(4x+12) = \frac{1}{4}(4x+12) -3 = x+3 -3[/tex]

Simplify:

g(f(x)) = x                for all x

⇒  g(x) is the inverse of f(x)

Therefore, [tex] g(x)=\frac{1}{4}x-3[/tex]

Using inverse functions, it is found that that:

[tex]g(x) = \frac{x - 12}{4}[/tex]

To find the inverse function, we exchange x and y in the original function, then isolate f.

The function f(x) is given by:

[tex]f(x) = 4x + 12[/tex]

Function g(x) is the inverse of f(x), then:

[tex]y = 4x + 12[/tex]

[tex]x = 4y + 12[/tex]

[tex]4y = x - 12[/tex]

[tex]y = \frac{x - 12}{4}[/tex]

[tex]g(x) = \frac{x - 12}{4}[/tex]

To learn more about inverse functions, you can take a look at https://brainly.com/question/16485117